Spatial Economics of Information Flow between Head and Branch Offices - Toshiaki Takita (European Regional Science Association (ERSA), 2005)
This paper aims to develop a new spatial economic model for analyzing information flow between head and branch offices. The hierarchy between head and branch offices is modeled, and a way of treating information flow is proposed. Broadband Internet enables both home and office to send and receive much more information using personal computers, and the resulting changes and possibilities deserve analysis. This paper sets out how to decide the location of the head office and some branch offices, and the allocation of all employees and computers to head and branch offices. Also, an inter-regional Information Input-Output Table (Information IO Table) is proposed to express the information flow between the head office and the branch offices and between those offices and other enterprises.
Keywords: 330